Experimental Study on Fracture Propagation Mechanism of Shale Oil Reservoir of Lucaogou Formation in Jimusar - Jianmin Li; Yushi Zou; Shanzhi Shi; Shicheng Zhang; Junchao Wang; Xinfang Ma; Xiaohuan Zhang (Geofluids)
The lithology of shale oil reservoir of Lucaogou Formation in Junggar Basin, China shows great variation in a vertical direction and develops bedding planes (BPs). In such formation, rock properties and fabrics have a significant impact on stimulation effects. To clarify the fracture propagation mechanism in a vertically heterogeneous reservoir, an experimental study on fracture propagation in layered rock samples with complex lithology has been conducted. The effect of layers on the height of hydraulic fractures (HFs) was analysed based on triaxial hydraulic fracturing simulation system combined with mineral and mechanical characteristics analysis. The research shows that when the HF is initiated in siltstone layer, it tends to penetrate BPs with the dimensionless fracture height of more than 0.74. When HF is initiated in mudstone layer, the vertical growth of HFs tends to be terminated at the BPs, and thefracture height is constrained. The greater the thickness of the interlayer is, the more likely the HFs tend to be cut off at the interface and propagate along the interface, resulting in the limited fracture height. Under high horizontal stress difference, HFs are relatively straight. Due to the high permeability of BPs and the low viscosity of fracturing fluid, the fluid leakoff into BPs is observed, which is not conducive to the vertical propagation of HFs. Increasing the viscosity of fracturing fluid facilitates HFs to penetrate the high-permeability BPs and improves the vertical stimulated volume of shale oil reservoir.